Clinical and Neuropsychological Correlates of Prefrailty Syndrome - Lorenzo-López, Laura; Blanco-Fandiño, Julia; Cibeira, Nuria; Buján, Ana; López-López, Rocío; Maseda, Ana; Millán-Calenti, José Carlos (Frontiers in Medicine, 2020)
Physical frailty is closely associated with cognitive impairment. We aim to investigate the neuropsychological profiles of prefrail and nonfrail dementia-free community-dwelling older adults using a comprehensive neuropsychological evaluation, and to examine the association between specific frailty criteria and clinical and neuropsychological scores. Participants completed a comprehensive standardized neuropsychological evaluation (covering cognitive domains such as memory, executive functions, language and attention), and frailty assessment. Frailty was assessed according to biological criteria: unintentional weight loss, exhaustion, low physical activity, slowness, and weakness. The sample comprised 60 dementia-free community-dwelling adults, aged 65 years or older (range 65-89 years; 60.0% women). Forty-two participants were classified as robust (no frailty criteria present), and 18 as prefrail (1 or 2 frailty criteria present). We explored neurocognitive differences between the groups and examined the association between specific criteria of frailty phenotype and clinical and neuropsychological outcomes with bivariate tests and multivariate models. Prefrail participants showed poorer cognitive performance than nonfrail participants in both memory and non-memory cognitive domains. However, delayed episodic memory was the only cognitive subdomain that remained significant after controlling for age, gender and educational level. Gait speed was significantly associated with general cognitive performance, immediate memory, and processing speed, while grip strength was associated with visual episodic memory and visuoconstructive abilities. Both gait speed and grip strength were negatively associated with depressive scores. Our results suggest that prefrailty is associated with cognitive dysfunction. The fact that specific cognitive domains may be susceptible to subclinical states of physical frailty may have important clinical implications. Indeed, early detection of specific cognitive dysfunctions may allow opportunities for reversibility.